Passivating 1T′-MoTe2 multilayers at elevated temperatures by encapsulation. Issue 37 (18th September 2017) - Wang, Dennis; Smyser, Kori; Rhodes, Daniel; Balicas, Luis; Pasupathy, Abhay; Herman, Irving P.
Abstract : The decomposition of 1T′-MoTe2 at high temperatures can be slowed down substantially by encapsulating it with hBN. Abstract : Several-layer 1T′-MoTe2 decomposes very little during heating up to ∼550 °C under flowing argon when encapsulated by multilayer hBN, as monitored by Raman scattering and optical microscopy, but largely decomposes at much lower temperatures in incompletely covered and uncovered regions. In covered regions there are small amounts of tellurium product above ∼250 °C.